Mesenchymal stem/stromal cells- a principal element for tumour microenvironment heterogeneity - Sun, Li; Yao, Yongliang (Frontiers in Immunology, 2023)
The heterogeneity of the tumor microenvironment (TME) is a major obstacle in cancer treatment, making most therapeutic interventions palliative rather than curative.Previous studies have suggested that the reason for the low efficacy of immunotherapy and the relapse of the original responders over time may be due to the complex network of mesenchymal stem/stromal cells (MSCs), a population of multipotent progenitor cells existing in a variety of tissues. Cancer-associated MSCs (CA-MSCs) have already been isolated from various types of tumors and are characterized by their vigorous protumorigenic functions. Although the roles of CA-MSCs from different sources vary widely, their origins are still poorly understood. Current evidence suggests that when local resident or distally recruited MSCs interact with tumor cells and other components in the TME, "naïve" MSCs undergo genetic and functional changes to form CA-MSCs.In this review, we mainly focus on the multiple roles of CA-MSCs derived from different sources, which may help in elucidating the formation and function of the entire TME, as well as discover innovative targets for anti-cancer therapies.